Retrovirus-mediated transduction of a cytosine deaminase gene preserves the stemness of mesenchymal stem cells - Sung Park, Jin (Nature Publishing Group, 2013)
Human mesenchymal stem cells (MSCs) have emerged as attractive cellular vehicles to deliver therapeutic genes for ex-vivo therapy of diverse diseases; this is, in part, because they have the capability to migrate into tumor or lesion sites. Previously, we showed that MSCs could be utilized to deliver a bacterial cytosine deaminase (CD) suicide gene to brain tumors. Here we assessed whether transduction with a retroviral vector encoding CD gene altered the stem cell property of MSCs. MSCs were transduced at passage 1 and cultivated up to passage 11. We found that proliferation and differentiation potentials, chromosomal stability and surface antigenicity of MSCs were not altered by retroviral transduction. The results indicate that retroviral vectors can be safely utilized for delivery of suicide genes to MSCs for ex-vivo therapy. We also found that a single retroviral transduction was sufficient for sustainable expression up to passage 10. The persistent expression of the transduced gene indicates that transduced MSCs provide a tractable and manageable approach for potential use in allogeneic transplantation.